The Implementation of the International Baccalaureate Curriculum in an Inclusive Classroom : Implementasi Kurikulum International Baccalaureate dalam Kelas Inklusif - Sulthon Falah Hasan El Haq; Sabariyanto (Language Development Center, 2025)
Background: Inclusive education requires curriculum models that are responsive to diverse student needs. The International Baccalaureate (IB) Middle Years Programme (MYP) is one such curriculum that emphasizes inquiry-based learning, student-centered approaches, and global-mindedness, making it potentially suitable for inclusive settings. Purpose: This study aims to describe the implementation of the IB MYP curriculum in inclusive classrooms at Al-Firdaus Junior High School in the 2025 academic year. Method: A qualitative research approach with a case study design was employed. Data were collected through observations, in-depth interviews with subject teachers, homeroom teachers, and curriculum coordinators, and document analysis. Results and Discussion: The findings reveal that learning planning is conducted collaboratively through structured forums such as three-way conferences and collaboration meetings. These involve teachers, students, and parents in setting individual learning goals and adjusting learning plans based on student profiles and needs. During implementation, inquiry-based and participatory strategies are used to actively involve all students, including those with special needs. Homeroom teachers play a crucial role in offering individualized support, instructional adaptations, and emotional support. Evaluation emphasizes individual progress through personalized assignments and portfolios. Key supporting factors include continuous teacher training, collaborative teaching culture, and strong school policy support. Conclusions and Implications: The study confirms that the contextual and collaborative implementation of the IB curriculum fosters an inclusive, responsive, and transformative learning environment. These findings suggest that schools aiming for inclusive practices can benefit from adopting the IB framework with tailored strategies and strong institutional support